Inkberry, Ilex glabra - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Inkberry is found throughout Florida and more broadly west to Texas and northeast to the Canadian border. Fruits attract birds and other wildlife but are not edible to humans. Flowers attract pollinators, including honey bees. Plant male and female plants in order to sustain fruit production. https://edis.ifas.ufl.edu/sg171